PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN SISWA BERSEKOLAH DI SEKOLAH ISLAM TERPADU - Heny Mulyani; Heri Khoiruddin; Marwah Hasanah (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2022)
Competition among educational institutions, resulting in a minimum number of students enrolled. In addition, the pandemic conditions that occurred also influenced consumers in choosing educational institutions. Even in various areas, private schools are threatened with closure due to the pandemic, which has reduced people's interest in sending their children to private schools. The purpose of this study was to find out: how does the marketing mix influence students' decisions to attend Adzkia Integrated Islamic School, how much influence does the marketing mix have on students' decisions to attend Adzkia Integrated Islamic School. This type of research is a quantitative research with ex post de facto method. The population in this study were Adzkia Sukabumi IT Middle School and High School students. The data collection technique uses an instrument in the form of a questionnaire. Before being used to obtain objective data, the validity and reliability of the questionnaire was first carried out. After the data is collected, then the data is processed and analyzed using the classical assumption test and simple linear regression analysis techniques. The results of this study indicate that the marketing mix which consists of product, price, promotion, place, people, physical evidence, and process has a significant influence on students' decisions to attend Adzkia Integrated Islamic School with a tcount of 3.854 greater than the ttabel value 1.665 with a significance value of 0.00 <0.05. While the coefficient value of the adjusted R aquare shows that the marketing mix has an influence of 16.5% with a calculation of 100% -16.5%, then 83.5% is another factor that influences students' decisions in choosing to study at SIT Adzkia Sukabumi